Storytelling Sebagai Strategi Healing Dakwah: Analisis Content Dakwah Ustadz Hilman Fauzi - Nurul Fadilah; Yoga Basyiril Sabirin; Canra Krisna Jaya (Jurnal Al-Hikmah: Jurnal Dakwah, 2025)
Abstract: This study aims to analyze the content of Ustadz Hilman Fauzi's preaching in digital preaching and explain the role of storytelling strategies in shaping Islamic messages, the healing process of preaching, and its transformative dimensions for Muslim female audiences. The background of this study stems from the increasing spiritual and emotional needs of Muslim women in the digital age who face psychological and social pressures and the influence of popular culture. This study uses a qualitative approach with content analysis methods on the comments of Muslim female audiences on Ustadz Hilman's preaching videos on the TikTok platform. The data is categorized into several themes, namely the acceptance of Islamic messages, emotional responses, perceptions of healing, and the spiritual experiences of the audience. The results of the analysis show that the content analysis of the storytelling da'wah used by Ustadz Hilman Fauzi in digital da'wah plays an important role in the healing process of da'wah for Muslim female audiences. Through real stories, personal experiences, and simple parables delivered in a light and interactive manner, Islamic messages become easier to understand and touch the emotional side of the audience. Storytelling has proven to be effective in creating a calming preaching space, building social solidarity, and strengthening spiritual closeness to Allah. Thus, storytelling is not only a method of conveying messages, but also a transformative da'wah strategy that integrates cognitive, emotional, social, and spiritual aspects into a holistic religious experience.Abstrak: Penelitian ini bertujuan untuk menganalisis konten dakwah Ustadz Hilman Fauzi dalam dakwah digital serta menjelaskan peran strategi storytelling dalam membentuk pesan Islami, proses healing dakwah, dan dimensi transformatifnya bagi audiens muslimah. Latar belakang penelitian berangkat dari meningkatnya kebutuhan spiritual dan emosional perempuan muslim di era digital yang menghadapi tekanan psikologis, sosial, dan pengaruh budaya populer. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis konten (content analysis) terhadap komentar audiens muslimah pada video dakwah Ustadz Hilman di platform TikTok. Data dikategorikan ke dalam beberapa tema, yaitu penerimaan pesan Islami, respon emosional, persepsi terhadap healing, serta pengalaman spiritual audiens. Hasil analisis menunjukkan bahwa analisis konten dari dakwah storytelling yang digunakan Ustadz Hilman Fauzi dalam dakwah digital berperan penting dalam proses healing dakwah bagi audiens muslimah. Melalui kisah nyata, pengalaman pribadi, dan perumpamaan sederhana yang disampaikan secara ringan dan interaktif, pesan Islami menjadi lebih mudah dipahami dan menyentuh sisi emosional audiens. Storytelling terbukti mampu menciptakan ruang dakwah yang menenangkan, membangun solidaritas sosial, serta memperkuat kedekatan spiritual dengan Allah. Dengan demikian, storytelling tidak hanya menjadi metode penyampaian pesan, tetapi juga strategi dakwah transformatif yang mengintegrasikan aspek kognitif, emosional, sosial, dan spiritual dalam satu pengalaman religius yang utuh.